2014
DOI: 10.1007/s10549-014-3002-y
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, diabetes, and triple-negative breast cancer prognosis

Abstract: Higher body mass index (BMI) and diabetes are associated with worse breast cancer prognosis. However, few studies have focused on triple-negative breast cancer (TNBC). The goal of this study is to examine this association in a cohort of patients with TNBC. We retrospectively reviewed 501 consecutive patients with TNBC seen at the Washington University Breast Oncology Clinic. Cox proportional hazard models were used to determine the relationship between BMI and diabetes at diagnosis with overall survival (OS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 33 publications
2
40
1
6
Order By: Relevance
“…All of the included articles were published from 2001 to 2016. Of the 17 articles, 3 studies [26,28,32] had a prospective cohort design, 10 studies [1723,27,29,30] had a retrospective cohort design, and 4 studies [24,25,31,33] had a case–control design. The total number of breast cancer patients was 48,315, with study populations ranging from 378 to 6342 in the individual articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the included articles were published from 2001 to 2016. Of the 17 articles, 3 studies [26,28,32] had a prospective cohort design, 10 studies [1723,27,29,30] had a retrospective cohort design, and 4 studies [24,25,31,33] had a case–control design. The total number of breast cancer patients was 48,315, with study populations ranging from 378 to 6342 in the individual articles.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies [1722,2428,3033] reported the effect of diabetes on the OS in female breast cancer patients. The study by Hou et al [25] provided risk estimate of OS with metformin or without metformin treatment; we therefore pooled the risk estimate, separately.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings also revealed that high BMI breast cancer was more likely to be ER/PR-positive compared with the low BMI group. However, some studies have suggested that overweight breast cancer patients are more likely to be associated with ER-negativity, TNBC, or histological grade III [14, 15]. A recent study showed that overweight (BMI > 24 kg/m 2 ) women with TNBC have a shorter OS [16].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with increased risk of breast cancer recurrence and mortality in both pre and postmenopausal women (83,84). Multiple studies have demonstrated that this association may be stronger in women with hormone receptor-positive tumors (85)(86)(87).…”
Section: Cancermentioning
confidence: 99%